The chaperone [compact disc, unabridged] - Moriarty, Laura, 1970- (Penguin Audio, 2012)
A novel about the friendship between an adolescent, pre-movie-star Louise Brooks, and the 36-year-old woman who chaperones her to New York City for a summer, in 1922, and how it changes both their lives.